Expression of a hindlimb-determining factor Pitx1 in the forelimb of the lizard Pogona vitticeps during morphogenesis. Issue 10 (October 2016) - Melville, Jane; Hunjan, Sumitha; McLean, Felicity; Mantziou, Georgia; Boysen, Katja; Parry, Laura J.
Abstract : With over 9000 species, squamates, which include lizards and snakes, are the largest group of reptiles and second-largest order of vertebrates, spanning a vast array of appendicular skeletal morphology. As such, they provide a promising system for examining developmental and molecular processes underlying limb morphology. Using the central bearded dragon ( Pogona vitticeps ) as the primary study model, we examined limb morphometry throughout embryonic development and characterized the expression of three known developmental genes ( GHR, Pitx1 and Shh ) from early embryonic stage through to hatchling stage via reverse transcription quantitative polymerase chain reaction (RT-qPCR) and immunohistochemistry (IHC). In this study, all genes were found to be transcribed in both the forelimbs and hindlimbs of P. vitticeps. While the highest level of GHR expression occurred at the hatchling stage, Pitx1 and Shh expression was greatest earlier during embryogenesis, which coincides with the onset of the differentiation between forelimb and hindlimb length. We compared our finding of Pitx1 expression—a hindlimb-determining gene—in the forelimbs of P. vitticeps to that in a closely related Australian agamid lizard, Ctenophorus pictus, where we found Pitx1 expression to be more highly expressed in the hindlimb compared with the forelimb during early and late morphogenesis—a result consistent with that found across other tetrapods. Expression of Pitx1 in forelimbs has only rarely been documented, including via in situ hybridization in a chicken and a frog. Our findings from both RT-qPCR and IHC indicate that further research across a wider range of tetrapods is needed to more fully understand evolutionary variation in molecular processes underlying limb morphology.